Study on the Relationship of Firm’s Performance with Capital Structure-Evidence from Taiwan - Shailender Singh; Amar Singh (International Journal of Economics and Financial Issues, 2018)
The purpose of this study is to investigate the relationship between capital structure and firm’s financial performance by using five years data from 2011 to 2016 of Taiwan exchange listed companies. The data has been analyzed by using descriptive statistics, correlation analysis to find out the association between the variables and t-statistics to test the hypothesis. The findings at overall market as well as sector levels were unspectacular but remarkably consistent. Capital structure and various financial parameters exhibit correlation coefficients that were mixed in signs with relatively weak correlation strength. Further the results suggest that t-test statistics registered statistical insignificance for the three research objectives. Keywords: Capital Structure, Financial Performance, Leverage Ratio, TWSE. JEL Classifications: C32, C180, F43